EFL Students' Course Content Practices between Conventional and Blended Learning - Hadiyanto Hadiyanto (Edukasi, 2021)
Blended learning has increasingly been applied in higher education. The present study investigated the students' perception toward the practices of course content between conventional and blended learning. The study's design was a survey design conducted on second and third-year students. The students perceived that blended learning allows a wider chance to students to explore and practice their course knowledge and skills than conventional learning. Furthermore, the students perceived that the practices of course knowledge and skills in blended learning significantly contributed to their CGPA. However, the course knowledge and skills practices in conventional learning yielded a low effect on students' CGPA. This study implicates that applying blended learning in a course optimizes EFL students' course content competencies and increases their CGPA.